Metabolites from the endophytic fungi : Botryosphaeria rhodina PSU-M35 and PSU-M114 and Penicillium sclerotiorum PSU-A13 - Jiraporn Arunpanichlert (Prince of Songkla University, 2010)
Thesis (M.Sc., Organic Chemistry)--Prince of Songkla University, 2009